The chronopharmacological effect of curcumin on human gall-bladder (Faculty of Medicine Universitas Indonesia, 2001)
Human gallbladder physiologically contracts and relaxes periodically. It has been demonstrated that curcumin (C) an active compound of Curcuma xanthorrhiza and Curcuma domestica produces a positive cholekinetic effect. The objective of this study is to define the influence of physiologic contraction and refilling of human gallbladder on the cholekinetic effect of Curcumin, and to determine the rime to achieve the maximum gall-bladder contraction after administration of 40 mg curcumin. Twelve healthy volunteers ingested 40 mg C and placebo (P) in a randomized double blind cross over study design. The volumes of gallbladder before and after taking C and P were half hourly determined by utrasonography and calculated using the ellipsoid methad for 6.0 hours. After P administration there is no gallbladder contraction. While afier C administration there was a contraction phase for 2 hours followed by a refilling phase for another 2.5 hours and then followed by second gall-bladder contraction started for 4.5 up to 6.0 hours. The maximal volume of gallblndder after 6.A hours was less than the basal volume, The cholekinetic effect of C is not chronopharmacologically influenced by the gall-bladder physiologic periodic contraction and refilling. The maximum contraction effect of C was achieved at 2 hours after oral administraion. (Med J Indones 2001; 10: 219-23)